Метод автоматичного проектування раціональних схем розкрою рулонних матеріалів на деталі взття - Chuprinka, V.I.; Chebanyuk, E.V. (Інститут програмних систем НАН України, 2015)
The basic structural components of task automatic computer-aided design of effective cutting schemas of roll material on shoes details with taking into account packaged output are dedicated. The mathematical models of this structural components are represented. This models help to implement effective methods of automatic computer-aided design of cutting schemas roll material on shoes details.